2020
DOI: 10.1016/j.jsg.2019.103952
|View full text |Cite
|
Sign up to set email alerts
|

Bed-parallel slip: Identifying missing displacement in mass transport deposits

Abstract: Bed-parallel slip (BPS), where neighbouring beds slide past one another along bedding planes, is notoriously difficult to identify without reference to pre-existing features such as steep faults or dykes that act as markers to record BPS offset. While BPS is intuitively thought to operate during downslope sliding of mass transport deposits (MTDs) in sedimentary basins, there is a conspicuous lack of supporting outcrop or seismic data to corroborate this and BPS displacement may therefore have remained unaccoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 75 publications
3
15
0
Order By: Relevance
“…Microstructural and outcrop observations indicate that shearing (and eventually opening) occurred along the BPFs during normal faulting and before folding. This is in line with the results of recent publications that describe BPFs associated with normal faults in shallow dipping sequences (<10°; Delogkos et al, 2017;Alsop et al, 2020). Shearing in such conditions appear mechanically unfavourable and can be related to several driven mechanisms.…”
Section: Mechanical Insight Into Bedding-parallel Faulting In Sedimentary Rockssupporting
confidence: 91%
See 2 more Smart Citations
“…Microstructural and outcrop observations indicate that shearing (and eventually opening) occurred along the BPFs during normal faulting and before folding. This is in line with the results of recent publications that describe BPFs associated with normal faults in shallow dipping sequences (<10°; Delogkos et al, 2017;Alsop et al, 2020). Shearing in such conditions appear mechanically unfavourable and can be related to several driven mechanisms.…”
Section: Mechanical Insight Into Bedding-parallel Faulting In Sedimentary Rockssupporting
confidence: 91%
“…The shear movements during the extensional regime confirm other publications showing that BPFs may form in such context for a limited local tilting of the bedding (<10°) (Smart et al, 2009;Delogkos et al, 2018;Alsop et al, 2020). The movements on the BPFs could be attributed to a flexural slip mechanism due to normal fault-related folding (Watterson et al, 1998;Ferrill et al, 2007;Smart et al, 2009;Delogkos et al, 2018) or to gravity-driven downslope deformations (e.g., Alsop et al, 2020). The latter is unlikely in the studied areas, considering that the rocks have been deeply buried before the formation of the BPF.…”
Section: Driving Mechanisms Behind Bpf Formation At the Regional Scalesupporting
confidence: 89%
See 1 more Smart Citation
“…The coring site is located close to the top of the Jianshan Anticline and we here interpret detachment surfaces preserved in the core as failure surfaces formed toward the head scarp of seismic-induced slumps that translated downslope from the anticlinal crest. Similar gravity-driven bedding-parallel detachment surfaces generated by the downslope-directed failure of sediments have been recently recorded in outcrops from the Dead Sea (Alsop et al, 2020).…”
Section: Type Vi: Detachment Surfacessupporting
confidence: 75%
“…We have previously suggested that detrital marker beds act as barriers or baffles to fluid flow, thereby forming seals to overpressured sediment that fails directly beneath it and locally fluidizes to create injected gouge (Alsop et al, 2018a). Mechanical heterogeneity linked to alternating detrital and aragonite layers, combined with variations in fluid pressure are thought to be the likely controls on positioning of both the basal and upper detachments, and bed-parallel slip planes in general (Alsop et al, 2020d). Thus, we interpret the aragonite-rich sediment above the uppermost (blue) detrital as fluid rich and weak due to being non-compacted and close to the sediment surface, while the aragonite-rich layers below the marker were overpressured and failed.…”
Section: What Factors Influence Detachments In Fats?mentioning
confidence: 99%